Methodological issues in yoga therapy research among psychiatric patients - Rama Reddy Karri; Ananda B. Bhavanani; Meena Ramanathan; Vijaya Gopal Mopidevi (Indian Journal of Psychiatry)
Yoga therapy has been widely accepted as part of the evidence-based modern healthcare system. Although research publications are growing in leaps and bounds, many methodological issues pose stumbling blocks. In this narrative review, various issues like standalone or add-on treatment, blinding, randomization, nature of dependent and intervening variables, duration of intervention, sustainability of effects, attrition bias, adherence and accuracy, all or none performance, diverse schools, heterogeneity and multidimensionality, assortment, permutations, and combinations of different components, neglect of essential ingredients, mindfulness, catch-22 situation, credentials of the instructors, cultural factors, naivety, multicentric studies, duration of collection of data, primary or standard treatment, interdisciplinary research, statistical lapses, qualitative research, biomedical research are discussed. There is a need to frame guidelines for conducting yoga therapy research and publication.